ANALYSIS OF RHODAMIN B AND METHANYL YELLOW IN SCHOOL CANTEEN SNACKS IN THE SELINDUNG HEALTH CENTER AREA OF PANGKALPINANG CITY IN 2024 - Puspitasari, Puteri; Kurrohman, Taufik; Kusmadeni, Deri (HEARTY, 2025)
The Government of Indonesia through the Regulation of the Minister of Health (Permenkes) No.239/Menkes/Per/V/85 stipulates 30 dangerous dyes. Rhodamin B and Methanyl Yellow are among the dyes that are declared as dangerous dyes and are prohibited from being used in food products. Illegal food additives such as Methanyl yellow and Rhodamin B dyes are able to attract buyers' eyes. The location of this research was carried out in the Canteen of SDN 6, SDN 22, Pangkalpinang, and SMPN 7 Pangkalpinang, the researcher sampled snacks with the School Canteen at the Tahfizh al-Quran Attauhid Islamic Foundation, namely SD Islam Tahfizh al-quran Attauhid and SMP Santo Paulus Pangkalpinang which is one of the Private Schools that are members of Kindergarten, Elementary School and Junior High School in Gabek District. The current situation of school canteens in the city of Pangkalpinang is still found with several colorful canteen snacks such as packaged ice, food skewered with snack skewers, instant drinks, packaged snacks and instant noodles. This assessment aims to find out Rhodamin B and Methanyl Yellow in the School Canteen Snacks of the Selindung Health Center Work Area, Pangkalpinang City. This research method is an experimental method by conducting an examination of snack food samples at the Bangka Regency Health Laboratory with a sample of 20 samples consisting of 12 food samples, 8 beverage samples spread across 3 elementary schools and 2 junior high schools in the Selindung Health Center working area. From the results of the examination of the Bangka Regency Health Laboratory, 20 samples consisting of 12 food samples and 8 beverage samples, all of which were found to be harmful Dyes, namely Rhodamin B and Methanyl Yellow. There is no content of Rhodamin B and Methanyl Yellow in School canteen snacks in the work area of the Selindung Health Center, Pangkalpinang City and is safe for consumption.